An Infected Mediastinal Cyst. Issue 2 (3rd April 2000) - Lawson, Lindsay M; Mason, Andrew C
Abstract : The authors describe a 43-year-old patient who had a mediastinal mass that became infected after a transbronchial needle aspirate biopsy. A paraspinal, extrapleural window with a saline-lidocaine mixture was created that allowed the placement of a percutaneous drainage catheter into the infected lesion. This procedure resulted in an excellent clinical outcome, and obviated the need for a thoracotomy and more invasive surgical management.